Learn to program with small basic an introduction to programming with games, art, science, and math - Marji, Majed; Price, Ed 1978- (No Starch Press, 2016)
"An introduction to programming with Small Basic, the free programming language for beginners based on BASIC and created by Microsoft. Covers topics like storing and manipulating data with variables; processing user input to make interactive programs; if/else statements; loops; and subroutines. Each chapter includes practice examples."